Body Image dengan Penyesuaian Diri pada Ibu Primigravida - Erfiani Mail; Farida Yuliani; Fitria Edni Wari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
The first pregnancy is experience of life that makes the big social and psychological change. The purpose of this study is to see whether body image has relationship with self adjustment in the primigravida. Design of this study is a cross-sectional analytical study, it has two variables, independent variables (body image) and the dependent variable (self adjustment). The subject of this study is 30 primigravida using simple random sampling technique, and data used are primary data with instruments such as questionnaires and the data analyzed with the Fisher exact test. It had been done in PMB F at Desa Gayaman Mojoanyar sub-district Mojokerto regency on September. The results show that most primigravida whose body image have positively get 22 people (73.3%) and self adjustment do well consist of 19 people (63, 3%). The data analyzed by Fisher exact with significant level of 5% (0.05) are taken by value p(0.001) <α (0.05) means that body image has relationship with self adjustment in primigravida. The pregnancy should be faced by the best self adjustment in order to keep either psychological or physical in pregnant women and their fetus well.